Tuberkulosis Gumma pada Pasien Tuberkulosis Paru - Donytasari, Fitri Meutia; Dalimunthe, Dina Arwina; Siregar, Remenda (Talenta Publisher, 2024)
Background: Tuberculosis (TB) gumma (metastatic tuberculous abscess) is a rare form of cutaneous TB, generally occurring in malnourished and immunocompromised patient. Case: A 24 year old man with a chief complaint of ulcers accompanied by a thick pigmented crusts on the neck and left abdomen without pain since 3 months ago. Initially, 6 months ago a small skin coloured lump the size of a green bean seed arised on the stomach and neck, not itchy or painful. One month later, the mass got bigger, ulcerated, and pus drainage were seen. The patient was also currently diagnosed with pulmonary TB. Dermatological examination showed an ulcer with a diameter of 10 cm with crusts and pus with irregular edges and hyperpigmentation in the left colli region and an ulcer with a diameter of 15 cm with crusts and pus with irregular edges and hyperpigmentation in the left lumbar region. The results of histopathological examination of the dermis showed fibrocollagenous connective tissue with infiltration of inflammatory lymphocytes and PMN cells, localized clusters of epithelioid cells with central necrosis and Langhans multinucleated giant cells were found. Discussion: Gumma tuberculosis is a multibacillary variant of cutaneous TB with a focus on hematogenous spread. Antituberculosis drugs are given according to the phase and the dose is according to the patient's body weight. Conclusion: A case of gumma tuberculosis has been reported in an immunocompetent young adult patient with pulmonary tuberculosis. The prognosis in patients is generally good. Pendahuluan: Tuberkulosis (TB) gumma (abses tuberkulosis metastatik) adalah bentuk TB kutis yang jarang, umumnya terjadi pada keadaan malnutrisi dan imunokompromais. Kasus: Seorang laki-laki berusia 24 tahun dengan keluhan utama luka borok disertai dengan keropeng hitam yang tebal pada leher dan perut kiri yang tanpa rasa nyeri sejak 3 bulan lalu. Awalnya, 6 bulan yang lalu pasien merasakan adanya benjolan kecil seukuran biji kacang hijau pada perut dan leher yang sewarna kulit dan tidak terasa gatal maupun nyeri. Satu bulan setelahnya benjolan dirasakan semakin membesar kemudian pecah dan mengeluarkan nanah. Pasien saat ini juga didiagnosis dengan TB paru. Dari pemeriksaan dermatologis tampak ulkus dengan diameter 10 cm disertai krusta dan pus dengan tepi ireguler dan hiperpigmentasi pada regio colli sinistra dan ulkus dengan diameter 15 cm disertai krusta dan pus dengan tepi ireguler dan hiperpigmentasi pada regio lumbalis sinistra. Hasil histopatologis dari jaringan regio abdomen dekstra menunjukan bagian dermis terdiri dari jaringan ikat fibrokolageneus dengan infiltrasi sel-sel radang limfosit dan PMN, setempat tampak kelompokan sel-sel epiteloid dengan nekrosis sentral dan dijumpai Langhans multinucleated giant cell. Diskusi: Tuberkulosis gumma merupakan varian multibasiler dari TB kutis dengan fokus penyebaran secara hematogen. Obat antituberkulosis (OAT) diberiksan sesuai fase dan dosis disesuaikan dengan berat badan pasien. Kesimpulan: Telah dilaporkan satu kasus tuberkulosis gumma pada pasien dewasa muda imunokompeten yang mengalami tuberkulosis paru. Prognosis pada pasien umumnya baik.